The complete concert for George [videorecording (DVD)] - Leland, David, 1947-; Cooper, Ray, 1942-; Harrison, Olivia, 1948-; Kamen, Jon; Ferguson, Claire; Clapton, Eric; Shankar, Anoushka; Brown, Joe; Holland, Jools; Brown, Sam, 1939-1977; Lynne, Jeff; McCartney, Paul; et al. (Warner Music Group : Oops Pub., 2003)
Live benefit concert in memory of George Harrison in aid of The Material World Foundation.